Expression of HER2/NEU in newly diagnosed metastatic carcinoma prostate on TRUS biopsy specimen and its clinical correlation and progression. Issue 2 (May 2023) - Abhishek, Anand; Sarkar, Debansu; Kumar Pal, Dilip
Background: Prostate cancer development and progression to androgen-independent disease is correlated with increased expression of growth factors and receptors capable of establishing autocrine and/or paracrine growth-stimulatory loops. Overexpression of the Her2/neu receptor tyrosine kinase has been associated with the progression to androgen independence in prostate cancer cells. Objective: Our primary aim was to investigate the frequency of HER2/neu amplification in prostate biopsy specimens in newly diagnosed metastatic carcinoma prostate and its correlation to progression of androgen independent carcinoma. Materials and Methods: In our study, expression of HER2/neu was carried out by immunohistochemical analysis in TRUS biopsy specimen of newly diagnosed metastatic carcinoma prostate. Results: Out of 36 patients, seven (19.4%) showed her2neu overexpression on immunohistochemical staining. Five out of seven (71%) were associated with higher histological grade >7 at diagnosis ( p  < 0.05). Her2neu overexpression was not significantly associated with age and serum PSA at diagnosis. However progression to castration resistant stage was not dependant on Her2/neu status ( p  > 0.05). Conclusion: Overexpression of her2/neu was associated with high grade carcinoma prostate at diagnosis, however progression to castration resistant stage was not related with her2neu expression.